2023
DOI: 10.1108/tqm-01-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Consumer quality management for beverage food products: analyzing consumer’ perceptions toward repurchase intention

Abstract: PurposeThe research on consumerism has been dramatically rising in recent decades. However, in the food industry, little research has been empirically conducted in the beverage industry. This research empirically tests the consequences of consumer perceptions: perceived price (PPR), perceived quality (PQ), perceived packaging (PPG) and perceived taste (PT) on repurchase intention (RI) particularly; it unveils the consumer attributes, e.g. gender, age and ethnicity between consumer perceptions and RI of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(258 reference statements)
1
0
0
Order By: Relevance
“…In this case, when viewers argue or believe that the overall quality of the video that they watch was deemed satisfactory, exceeded expectations or good, then there’s a high chance that these same viewers will watch the same video in the future, and vice versa. This finding also matched the results obtained by previous studies that also found the significance of perceived quality in determining people’s intention and actual behavior (Dokcen et al , 2021; Khare and Pandey, 2017; Rosillo-Díaz et al , 2020; Sharif et al , 2023; Soh et al , 2017; Kaswengi and Lambey-Checchin, 2020; Bei and Chiao, 2006; Espejel et al , 2009).…”
Section: Resultssupporting
confidence: 91%
“…In this case, when viewers argue or believe that the overall quality of the video that they watch was deemed satisfactory, exceeded expectations or good, then there’s a high chance that these same viewers will watch the same video in the future, and vice versa. This finding also matched the results obtained by previous studies that also found the significance of perceived quality in determining people’s intention and actual behavior (Dokcen et al , 2021; Khare and Pandey, 2017; Rosillo-Díaz et al , 2020; Sharif et al , 2023; Soh et al , 2017; Kaswengi and Lambey-Checchin, 2020; Bei and Chiao, 2006; Espejel et al , 2009).…”
Section: Resultssupporting
confidence: 91%